Development and Validation of a Questionnaire to Uncover the Hidden Motivations Behind Adult Food Choices - Idri Iqra Fikha; Farah Faza; Unun Fitry Febria Bafani (Journal of Global Nutrition, 2026)
Background : The Covid-19 pandemic has changed the eating pattern and reasons for choosing foods among adults. To consider this change, we, therefore, adapted the original Food Choice Questionnaire (FCQ) before using it in the community. Methods : A cross-sectional study was conducted among 64 adults aged 35-64 years from December 2020 to January 2021 in Jakarta. Principal component analysis (PCA) was performed to reduce items in the original instrument with 36 questions. The Keiser Meyer Olkin (KMO) value must meet the value >0.5 to assess the feasibility of factor analysis. Question items included in the final FCQ shall have an anti-image value > 0.5 and a loading factor value < 0.4. Four focus group discussions (40 adults) were also performed to help confirm the question commonly mentioned by the subjects. Internal consistency of the scale was evaluated using Cronbach’s alpha. A criteria for Cronbach’s alpha was selected as 0.60. Test-retest reliability was examined by intraclass correlation coefficient (ICC). Results: The KMO and MSA value from 36 questions met the expected criteria. We removed 16 questions that did not meet the anti-image values and the loading factor criteria from the original version of FCQ. Two questions about maintaining body weight and low fat intake were confirmed from the FGD. The final item questions consisted of four components, namely (1) Mood and convenience, (2) Health and ethical concern, (3) Price and natural content, (4) Sensory appeal and Familiarity, weight control components. Internal validity and reliability testing showed that the adapted FCQ was valid and reliable to assess the food choice motive among adults. Conclusion: The adapted FCQ for adults living in Jakarta during the Covid-19 pandemic comprised of a shorter list of 18 questions with good internal validity and reliability, and can be used as a tool to assess food choice motives among adults living in Jakarta. Keywords: Adults, Covid-19, Food choice motives, Questionnaire